Nemytzki-Edelstein-Meir-Keeler Type Results in b-Metric Spaces. (4th July 2018) - Aydi, Hassen; Banković, Radoje; Mitrović, Ivan; Nazam, Muhammad
Abstract : We consider some Nemytzki-Edelstein-Meir-Keeler type results in the context of b-metric spaces. In some cases, we assume that the b-metric is continuous. Our results generalize several known ones in existing literature. We also present some examples to illustrate the usability of our results.